Virtual environments innovation and R&D activities: management challenges - Ale Ebrahim, N.; Ahmed, S.; Taha , Z. (2008)
Companies will not survive long unless they join a threefold revolution in management itself, innovation, and information technology. Innovation plays a central role in economic development, at regional and national level. In the competitive environment companies are obliged to produce more rapidly, more effectively and more efficiently in new product development which is a result of research and development (R&D) activities. It is necessary for them to put together different capabilities and services with the goal, through cooperation between suppliers and customers, service providers and scientific institutions to achieve innovations of high quality. Depending on the type of industry, the type of business, the type of innovation and the strategic objectives that have been set, firms will regularly have to modify the way in which their R&D and innovation is organized and how information technology should managed. Nowadays shift from serial to simultaneous and parallel working in innovation has become more commonplace. Literatures have shown that collaboration is as a meta-capability for innovation. This article after define a virtual teams and its characteristics, addressing virtual environments innovation and the relationship to R&D activities. Finally conclude that managers of company should invest less in tangible assets, but more in R&D and virtual team to generate knowledge, and in their employees’ creativity to stimulate incremental innovations in already existing technologies that will directly generate their future competitive advantage.